Molecular Studies of Relationships and Identifications Among Insects of the Subfamily Panchaetothripinae (Thysanoptera, Thripidae). Issue 5 (19th September 2022) - Xie, Yan Lan; Mound, Laurence A; Lima, Élison Fabrício Bezerra; He, Shu Qi; Zhang, Hong Rui; Li, Ya Jin
Abstract: The Panchaetothripinae comprises 42 genera and 146 species of leaf-feeding thrips, some of which are horticultural pests. We examined representatives of the 18 genera that include most of these pests. For species delimitation, we used DNA barcoding to produce171 sequences for 40 morphospecies. Most species were found to be monophyletic, although cryptic diversity was evident in 8 presumptive species. A multilocus molecular phylogenetic assessment was based on one mitochondrial ( COI ) and three nuclear loci ( EF-1α, ITS2, and 28S) from 132 specimens (18 genera and 33 species), representing all genera and 82% of species in China. Maximum likelihood (ML) and Bayesian inference (BI) confirmed monophyly of each genus with strong support. Monophyly of tribes Panchaetothripini and Monilothripini were refuted, but the well supported tribe Tryphactothripini was confirmed. Rhipiphorothrips was recovered as a sister to the remainder of the genera of Panchaetothripinae combined. Both analyses revealed two major clades. Clade A comprised the majority of the genera, including tribe Tryphactothripini. Clade B included only four genera of which two, Helionothrips and Caliothrips, are particularly species rich. The relationships of some genera remain unresolved.